Implementation of Paddy GHP with Farmer Support Capacity in Singaparna Sub-district - Rusmono, Momon; Kusuma Wardani, Intan; Elviyana Nurdiya Ningsih; Zahron Helmy; Alya Husnul Khotimah; Erniati (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2025)
Rice is the primary staple food in Indonesia, and one of the persistent challenges in its agricultural sector is maintaining both production quantity and quality, particularly during the post-harvest stage. To address this issue, the present study evaluates the implementation of Good Handling Practices (GHP) for rice and formulates strategies to enhance GHP adoption in alignment with the capacity and resources of rice farmers. The research was conducted from January to March 2025 in Singaparna District, Tasikmalaya Regency, involving 86 respondents selected from a population of 139 rice farmers using proportional random sampling. Data were analyzed using descriptive statistics and multiple linear regression analysis. The findings indicate that the implementation of GHP, supported by farmers’ capacity, is significantly influenced by the use of appropriate GHP technologies (coefficient = 0.518) and the effectiveness of agricultural extension services (coefficient = 0.179). In contrast, institutional support showed no statistically significant effect. Together, GHP and extension services explained 73.4% of the variance in GHP implementation. Recommended strategies for improving GHP adoption include increasing access to post-harvest handling facilities, particularly rice threshing equipment, applying diverse and context-specific extension methods tailored to farmers’ needs, utilizing suitable media for GHP dissemination, and strengthening both the role and frequency of agricultural extension activities. This study provides a basis for improving the application of GHP in rice farming by optimizing farmers’ capacity, ultimately reducing post-harvest losses, preserving grain quality, and supporting local food security.